Systematic Literature Review : Pengaruh Hasil Belajar Kewirausahaan dan Pelaksanaan Praktek Kerja Industri Terhadap Keputusan Rencana Karier Peserta - Octa Nilam Lukkita Aga; Zahara Tussoleha Rony (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
After graduating from vocational school, students must make decisions about their career plans that will be adjusted to their abilities. This career plan can be based on the influence of their education through internship and entrepreneurship activities, because in internship activities, students are required to become employees or workers in a company. Thoughtful career planning decisions will help students develop potential areas of expertise and prepare them for work. The research design used is quantitative correlation with data collection using literature research from journals, books, documents and other relevant sources. The results of this research also show that vocational school graduates who are involved in internship activities and study entrepreneurship have sufficient skills, but they still think as workers, not as business actors. The government is expected to be tougher in telling vocational school graduates that they can create their own jobs.